PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT BERBANTUAN MEDIA DIOSILIR TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD - Fanida Zahrotul Mufidah; Suyanti; Nur Antika Eky Hastuti, Dian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low science learning outcomes of fifth grade students at SDN Kare 01, Kare District, Madiun Regency, especially on the water cycle material. Learning activities that were still teacher-centered caused students to be less active and less able to understand learning concepts optimally. Therefore, learning models and media that can improve students’ activeness and understanding are needed. This study aimed to determine whether there was an effect of the Teams Games Tournament (TGT) cooperative learning model assisted by DIOSILIR media on the science learning outcomes of fifth grade students at SDN Kare 01. This study used a quantitative approach with a quasi-experimental research design. The research sample consisted of all fifth-grade students at SDN Kare 01, totaling 50 students, divided into 25 students of class VA as the experimental group and 25 students of class VB as the control group. Data collection techniques were carried out through tests, observations, and documentation. Data analysis techniques used normality tests, homogeneity tests, and hypothesis testing in the form of a t-test with the help of IBM SPSS Statistics 26. The results of the hypothesis test showed a significance value of 0.000 < 0.05, meaning that the Teams Games Tournament (TGT) cooperative learning model assisted by DIOSILIR media had a significant effect on the science learning outcomes of fifth grade students at SDN Kare 01, Kare District, Madiun Regency. The average score of students in the experimental group was higher than that of the control group.